Gut heavy metal and antibiotic resistome of humans living in the high Arctic - Hauptmann, Aviaja Lyberth; Johansen, Joachim; Stæger, Frederik Filip; Nielsen, Dennis Sandris; Mulvad, Gert; Hanghøj, Kristian; Rasmussen, Simon; Hansen, Torben; Albrechtsen, Anders (Frontiers in Microbiology, 2024)
Contaminants such as heavy metals accumulate in the Arctic environment and the food web. The diet of Indigenous peoples of North Greenland includes locally sourced foods that are central to nutritional, cultural and societal health but can contain high concentrations of heavy metals. While bacteria play an important role in the metabolism of xenobiotics, there are limited studies on the impact of heavy metals on the human gut microbiome and it is so far unknown if and how Arctic environmental contaminants impact the gut microbes of humans living in and off the Arctic environment. Using a multi-omics approach including amplicon, metagenome and metatranscriptome sequencing, we identified and assembled a near-complete genome of a mercury-resistant bacterial strain from the human gut microbiome, which expressed genes that are known to reduce the toxicity of mercury. At the overall ecological level assessed through alpha and beta diversity there was no significant effect of heavy metals on the gut microbiota. Through the assembly of a high number of near-complete metagenome-assembled genomes of human gut microbes we observed an almost complete overlap between heavy metal resistant strains and antibiotic resistant strains in which resistance genes were all located on the same genetic elements.